Neutrino oscillation in Weitzenbock space-time - Zhang, C. M. [UNESP] (My University, 2000)
In the framework of the teleparallel equivalent of general relativity, we obtain the evolution equation of the neutrino oscillation in vacuum. A comparison with the equivalent result of general relativity case, shows that the Dirac equation in Riemann and Weitzenbock space-times is equivalent in the spherical symmetric Schwarzschild space-time, but turns out to be different in the case of the axial symmetry.
Keywords: elementary particle; gravity; mathematical analysis; oscillation; space; theory; vacuum